2023
DOI: 10.3390/foods12142703
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Stabilized Emulsion Gels with Improved Emulsifying and Gelling Properties for the Delivery of Bioactive Ingredients: A Review

Abstract: In today’s food industry, the potential of bioactive compounds in preventing many chronic diseases has garnered significant attention. Many delivery systems have been developed to encapsulate these unstable bioactive compounds. Emulsion gels, as colloidal soft-solid materials, with their unique three-dimensional network structure and strong mechanical properties, are believed to provide excellent protection for bioactive substances. In the context of constructing carriers for bioactive materials, proteins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…Emulsion gels are usually prepared based on proteins, polysaccharides, or their mixtures, and the characteristics of oil droplets play a crucial role in the properties and functions of the system [ 148 ]. Emulsion gels, as colloidal solid materials, possess a unique three-dimensional network structure and strong mechanical properties, making them capable of providing excellent protection for bioactive substances [ 149 ]. Recently, a new method for preparing physically cross-linked starch-based emulsion gel beads using a water-in-oil emulsion gelation process was developed to effectively load procyanidins [ 150 ].…”
Section: Applications Of Procyanidins In Cartilage Injury After Acl Tearmentioning
confidence: 99%
“…Emulsion gels are usually prepared based on proteins, polysaccharides, or their mixtures, and the characteristics of oil droplets play a crucial role in the properties and functions of the system [ 148 ]. Emulsion gels, as colloidal solid materials, possess a unique three-dimensional network structure and strong mechanical properties, making them capable of providing excellent protection for bioactive substances [ 149 ]. Recently, a new method for preparing physically cross-linked starch-based emulsion gel beads using a water-in-oil emulsion gelation process was developed to effectively load procyanidins [ 150 ].…”
Section: Applications Of Procyanidins In Cartilage Injury After Acl Tearmentioning
confidence: 99%
“…At pH 7.83 (pI), the electrostatic charge on the collagen surface was almost zero, and the repulsive force between the droplets made it difficult to maintain emulsion stability, which resulted in the minimum ESI at the pI for collagen, with a V-shaped ESI curve. Therefore, by controlling the pH of the collagen solution system, collagen can be used as an emulsifier and potentially as a delivery material in food and pharmaceutical applications [36,37].…”
Section: Functional Properties 271 Emulsifying Activity Index (Eai) A...mentioning
confidence: 99%
“…According to Doan et al [5], in human nutrition, Spirulina finds favor not only for its remarkable protein content, which can reach up to 70% of its dry matter, but also for its composition of essential amino acids (AAs) and its high digestibility, positioning it as a promising alternative protein source. Moreover, proteins derived from microalgae exhibit favorable technological properties, serving as effective foaming, gelling, and emulsifying agents [6][7][8]. Numerous studies have demonstrated the competitive edge of microalgae proteins against commercially used emulsifiers like sodium caseinate, whey protein, and soy protein [9,10].…”
Section: Introductionmentioning
confidence: 99%